Thermo-acoustic catalytic effect on oxidizing woody torrefaction - Silveira, Edgar Amaral (2020)
The torrefaction (mild pyrolysis) process modifies biomass chemical and physical properties and is applied as a thermochemical route to upgrade solid fuel. In this work, the catalytic effect of thermo-acoustic on oxidizing woody torrefaction is assessed. The combined effect of two acoustic frequencies (1411, 2696 Hz) and three temperatures (230, 250, and 290 °C) was evaluated through weight loss and its deviation curves, calculated torrefaction severity index (TSI), as well as proximate, calorific, and compression strength analysis of Eucalyptus grandis. A new index to account for the catalytic effects on torrefaction (TCEI) was introduced, providing the quantitative analysis of acoustic frequencies influence. A two-step consecutive reaction numerical model allowed the thermo-acoustic experiment evaluation. For instance, the thermogravimetric profiles revealed that the acoustic field has a catalytic effect on wood torrefaction and enhances the biomass oxidation process for severe treatments. The kinetic simulation of the acoustic coupling resulted in faster conversion rates for the solid pseudo-components showing the boosting effect of acoustic frequencies in anticipating hemicellulose decomposition and enhancing second step oxidizing reaction.